2019
DOI: 10.1002/glia.23628
|View full text |Cite
|
Sign up to set email alerts
|

GPR124 regulates microtubule assembly, mitotic progression, and glioblastoma cell proliferation

Abstract: GPR124 is involved in embryonic development and remains expressed by select organs. The importance of GPR124 during development suggests that its aberrant expression might participate in tumor growth. Here we show that both increases and decreases in GPR124 expression in glioblastoma cells reduce cell proliferation by differentially altering the duration mitotic progression. Using mass spectrometry‐based proteomics, we discovered that GPR124 interacts with ch‐TOG, a known regulator of both microtubule (MT)‐plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Previous microscopy studies suggested that chTOG localizes to kinetochores ( Campbell et al, 2019 ; Gutiérrez-Caballero et al, 2015 ; Ryan et al, 2020 ), similar to the budding yeast ortholog ( Miller et al, 2016 ; Miller et al, 2019 ); however, it was unclear if this population was simply bound to microtubule tips. To address this, we used engineered HCT116 cells where the endogenous chTOG genes were epitope tagged with EGFP ( Cherry et al, 2019 ) to determine whether chTOG specifically localizes to kinetochores throughout mitosis ( Figure 1a ). We found that chTOG is largely excluded from the nucleus until prometaphase, when it appeared on kinetochores as assayed by co-localization with anti-centromere antibody (ACA) ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous microscopy studies suggested that chTOG localizes to kinetochores ( Campbell et al, 2019 ; Gutiérrez-Caballero et al, 2015 ; Ryan et al, 2020 ), similar to the budding yeast ortholog ( Miller et al, 2016 ; Miller et al, 2019 ); however, it was unclear if this population was simply bound to microtubule tips. To address this, we used engineered HCT116 cells where the endogenous chTOG genes were epitope tagged with EGFP ( Cherry et al, 2019 ) to determine whether chTOG specifically localizes to kinetochores throughout mitosis ( Figure 1a ). We found that chTOG is largely excluded from the nucleus until prometaphase, when it appeared on kinetochores as assayed by co-localization with anti-centromere antibody (ACA) ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…HCT116 ( Cherry et al, 2019 ), 293T ( Ding et al, 2013 ), and HeLa FlpIn Cells ( Etemad et al, 2015 ) cells were grown in a high-glucose DMEM (Thermo Fisher Scientific 11-965-118/Gibco 11965118) supplemented with antibiotic/antimycotic (Thermo Fisher Scientific 15240062) and 10% Foetal Bovine Serum (Thermo Fisher Scientific 26140095) at 37°C supplemented with 5% CO 2 . For microscopy experiments, cell suspensions were added to 35 mm wells containing acid washed 1.5 × 22 mm square coverslips (Fisher Scientific 152222) and grown for 12–24 hr prior to transfections or immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we used engineered HCT116 cells where endogenous chTOG alleles were epitope tagged with EGFP (Cherry et al, 2019) to determine whether chTOG specifically localizes to kinetochores throughout mitosis ( Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian cell culture HCT116 (Cherry et al, 2019), 293T (Ding et al, 2013), and HeLa FlpIn Cells (Etemad, Kuijt, & Kops, 2015) To entirely depolymerize the microtubule cytoskeleton, growth media were supplemented with 10 µM nocodazole (Sigma-Aldrich, M1404) for one hour. To synchronize cells, they were treated with 2.5 mM thymidine (Sigma-Aldrich, T9250) for 16 hours, cells were then placed in drug-free media for 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Despite multiple attempts to generate a homozygous knock-in for chTOG–FKBP–GFP, we only recovered heterozygous lines (more than twenty heterozygous clones in three separate attempts). Although there is a report of homozygous knock-in of chTOG–FKBP–GFP in HCT116 cells ( Cherry et al, 2019 ), we assume that homozygous knock-in of chTOG–FKBP–GFP in HeLa cells is lethal.
Fig.
…”
Section: Resultsmentioning
confidence: 87%